Human Rights and Gender Equality: An Analysis of Polygamy Regulations for Civil Servants in Indonesia - Yulia Fithriany Rahmah (Hukum Keluarga Islam IAIN LANGSA, 2025)
This research aims to analyze the regulations related to marriage and divorce permits for Civil Servants (PNS) in Indonesia as stipulated in Government Regulation of the Republic of Indonesia Number 45 of 1990. This regulation is often considered a new regulation, even though it has been in effect since 1983. The lack of legal awareness of this regulation has caused confusion in the community and sparked debate, mainly due to: (1) the lack of understanding and socialization related to this regulation, causing social chaos; (2) the assumption that the regulation is unfair because it contradicts Law Number 1 of 1974 concerning Marriage, especially in the provision of polygamy; and (3) potential violations of human rights, especially in relation to gender equality. This research uses a normative juridical method with a descriptive normative approach. The analysis is based on secondary legal sources, such as legislation and relevant literature. The results show that this regulation has urgency in upholding legal awareness in the community as a form of compliance with marriage rules for civil servants, especially in terms of polygamy permits for men and the prohibition of being a second wife for women. In addition, social chaos arising from this regulation can be prevented through strengthening legal awareness, which aims to create a better legal culture and increase compliance with applicable regulations. While this regulation is designed to provide legal protection for individuals and maintain ethics within the bureaucracy, its implementation must be in line with the principles of human rights and gender equality. Therefore, further evaluation of this regulation is needed so that it remains relevant to the social and legal dynamics developing in Indonesia.